2018
DOI: 10.3389/fnsyn.2018.00031
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling DISC1 × D2R Protein-Protein Interactions Facilitates Latent Inhibition in Disc1-L100P Animal Model of Schizophrenia and Enhances Synaptic Plasticity via D2 Receptors

Abstract: Both Disrupted-In-Schizophrenia-1 (DISC1) and dopamine receptors D2R have significant contributions to the pathogenesis of schizophrenia. Our previous study demonstrated that DISC1 binds to D2R and such protein-protein interaction is enhanced in patients with schizophrenia and Disc1-L100P mouse model of schizophrenia (Su et al., 2014). By uncoupling DISC1 × D2R interaction (trans-activator of transcription (TAT)-D2pep), the synthesized TAT-peptide elicited antipsychotic-like effects in pharmacological and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…We further found that TAT-D2pep restored the reduced spine density of D2R over-activated striatal neurons, indicating that the dendritic spines of the striatum could be therapeutic targets of this cell-penetrating peptide. In line with our results, increasing D2R-DISC1 complex formation caused by D2R over-activation has been recently demonstrated to decrease long term potentials in mouse hippocampus, indicating a role in synaptic plasticity (Lipina et al, 2018). To our knowledge, this is the first time that TAT-D2pep has been shown to reverse neurite impairment in vitro.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We further found that TAT-D2pep restored the reduced spine density of D2R over-activated striatal neurons, indicating that the dendritic spines of the striatum could be therapeutic targets of this cell-penetrating peptide. In line with our results, increasing D2R-DISC1 complex formation caused by D2R over-activation has been recently demonstrated to decrease long term potentials in mouse hippocampus, indicating a role in synaptic plasticity (Lipina et al, 2018). To our knowledge, this is the first time that TAT-D2pep has been shown to reverse neurite impairment in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…The following reagents were purchased: Quinpirole hydrochloride (Sigma Aldrich, St Louis, MO, United States), anti-MAP2 (1:1,000; Sigma Aldrich), anti-PSD-95 (1:1,000; Abcam, Cambridge, United Kingdom), anti-synaptophysin (1:1,000; Sigma Aldrich), anti-GSK3α/β (1:1,000; Cell Signaling Technology, Danvers, MA, United States), anti-phospho-GSK3β (Ser9) (1:1000; Cell Signaling Technology), anti-β-actin (1:5000; Millipore, Bedford, MA, United States), anti-GAD67 (1:800; Cell Signaling Technology), anti-D2R (1:400, Santa Cruz Biotechnology, CA, United States), anti-NPY (1:400, Santa Cruz Biotechnology), Alexa Fluor 568 Phalloidin (Invitrogen, Waltham, MA, United States), Alexa Fluor 488-conjugated goat anti-mouse IgG secondary antibody (1:400; Invitrogen) and Alexa Fluor 568-conjugated goat anti-rabbit IgG secondary antibody (1:400; Invitrogen), Cy3B-NHS (GE Healthcare, NSW, Australia), and Alexa Fluor 647-NHS (Thermo Fisher, Waltham, MA, United States). The region from K 211 to T 225 (KIYIVLRRRRKRVNT) of D2R is known to directly interact with DISC1 (Su et al, 2014;Lipina et al, 2018), which is used for designing TAT-D2peps. TAT-D2pep (YGRKKRRQRRR-KIYIVLRRRRKRVNT) and TAT-D2pep-negative control (NC; YGRKKRRQRRR) were synthesized by GenScript (GenScript, Hong Kong Ltd.), and dissolved in ultrapure water to a stock concentration of 10 mM.…”
Section: Antibodies and Chemicalsmentioning
confidence: 99%
“…A post-mortem study on the striatum of patients affected by schizophrenia demonstrated an increased interaction between D2R and DISC1 with the formation and accumulation of intraneural complexes [ 367 ]. They are involved in a potential neuroprotective effect, and also seem to exert a modulatory effect on synaptic plasticity, which is able to decrease long-term potentiation (LTP) in the hippocampus of mice [ 368 ]. Zheng and co-authors, using FRET and stochastic optical reconstruction microscopy (STORM) techniques in murine striatal neurons, demonstrated that the D2R-DISC1 complex is also able to influence intracellular signaling and affect the growth of dendritic spines.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently with these suggestions, the disruption of the D2R/DISC1 interaction has been found to reverse hyperactivity and prepulse Inhibition (PPI) aberrations in multiple rodent models of psychosis [ 143 ]. Finally, recent studies have demonstrated the involvement of DISC1 × D2R protein-protein interactions in the mechanisms of cognitive and synaptic plasticity and their modulation as pharmacological targets, contributing further insight into the molecular–cellular mechanisms of antipsychotic drugs [ 144 ].…”
Section: Resultsmentioning
confidence: 99%